Gender relations in adoption of Brachiaria fodder grass in Muhoroni, Rongo, Mbooni and Kilome sub-counties in Kenya - Njiru, Nelly; Galiè, Alessandra; Wanyoike, Francis N.; Mashonganyika, Tawanda; Boonabaana, Brenda; Bisikwa, Jeniffer; Njuguna-Mungai, Esther; Jones, Christopher S.; Baltenweck, Isabelle (International Livestock Research Institute, 2023)
Inadequate and poor-quality feed resources constrain livestock production that compromises the livelihoods dependent on livestock in low- and middle-income countries. Several forage varieties have been developed, targeting smallholder farmers in developing countries, yet the level of adoption remains low, particularly among women farmers. Adoption of varieties could enhance livelihoods by increasing livestock productivity and by providing income from the sale of surplus forage. Evidence on gendered barriers to, and incentives for, adoption of forage varieties is scarce. We explored the gender dynamics influencing uptake and commercialization of the Brachiaria grass forage variety among women and men farmers in four subcounties in Kenya. Data from 260 individuals, belonging to a household where at least one individual is a member of a dairy cooperative, were collected. Also, 16 single-sex focus group discussions and eight key informant interviews were undertaken. Results revealed Brachiaria grass is accessible to women and men. Dairy cooperatives are critical for women and men to access extension services, useful information, and planting materials, but only a few women are cooperative members. Men are constrained by small land areas, rather than the ownership and access problems that constrain women. These challenges privilege men while subordinating women and disenfranchizing them in terms of adopting this technology. Pathways for women’s and men’s empowerment exist through the sale of planting materials, hay bales, and an increased volume of milk obtained when cows are fed with Brachiaria. However, gender norms that reduce women’s engagement with cooperatives, and their access to and control over land, should be challenged.